Ekstrak Kulit Pisang Kepok (Musa paradisiaca) Menurunkan Kadar AST pada Tikus Putih yang Diinduksi Diet Tinggi Lemak - STEFANUS DJONI HUSODO; ASAMI RIETTA KUMALA; INDRI NGESTI RAHAYU (HANG TUAH MEDICAL JOURNAL, 2021)
ABSTRACT Background. Non-alcoholic fatty liver disease (NAFLD) is closely related to the incidence of obesity and dyslipidemia. Increased levels of Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) are the most frequently performed liver function tests that can be used as a benchmark for suspicion of NAFLD. Banana peels contain flavonoids and phenolics which are antioxidants that can function as hepatoprotectors. Aim. Proving the effect of Kepok banana peel extract on AST and ALT of Wistar rats induced high fat diet. Method. experimental study with a post-test only control group design, with four treatment groups. There is negative control group only given four weeks standard diet (K-), positive control group only given four weeks high-fat diet (K+), and two treatment group where the rats were given two weeks high-fat diet then were given two weeks high-fat diet plus Kepok banana peel extract at a dose of 200 mg/kg BW (K1) and 400 mg/kg BW (K2). Result. the highest mean AST levels were in the negative control group and the lowest was the K2 group. Meanwhile, the highest mean of ALT was in the positive control group and the lowest was the K2 group. Based on the Kruskal Wallis test, the significance of the AST variable was not different (p>0,05), but the ALT variable was significantly different (p<0,05). Significant differences from the Mann Whitney-U test (p<0,05) were obtained between the negative control group and the positive control, the negative control group with K2 and the positive control group with the K2 group). Conclusion. The administration of Kepok banana peel extract (Musa paradisiaca formatypica) showed a significant decrease in ALT levels in Wistar strain white rats induced by a high-fat diet, but it was not significant for AST levels